The Arabidopsis DREB2 genetic pathway is constitutively repressed by basal phosphoinositide-dependent phospholipase C coupled to diacylglycerol kinase - Djafi, Nabila; Vergnolle, Chantal; Cantrel, Catherine; Wietrzyński, Wojciech; Delage, Elise; Cochet, Françoise; Puyaubert, Juliette; Soubigou-Taconnat, Ludivine; Gey, Delphine; Collin, Sylvie; Balzergue, Sandrine; Zachowski, Alain; et al. (Frontiers in Plant Science, 2013)
Phosphoinositide-dependent phospholipases C (PI-PLCs) are activated in response to various stimuli. They utilize substrates provided by type III-Phosphatidylinositol-4 kinases (PI4KIII) to produce inositol triphosphate and diacylglycerol (DAG) that is phosphorylated into phosphatidic acid (PA) by DAG-kinases (DGKs). The roles of PI4KIIIs, PI-PLCs and DGKs in basal signalling are poorly understood. We investigated the control of gene expression by basal PI-PLC pathway in Arabidopsis thaliana suspension cells. A transcriptome-wide analysis allowed the identification of genes whose expression was altered by edelfosine, 30 µM wortmannin or R59022, inhibitors of PI-PLCs, PI4KIIIs and DGKs, respectively. We found that a gene responsive to one of these molecules is more likely to be similarly regulated by the other two inhibitors. The common action of these agents is to inhibit PA formation, showing that basal PI-PLCs act, in part, on gene expression through their coupling to DGKs. Amongst the genes up-regulated in presence of the inhibitors, were some DREB2 genes, in suspension cells and in seedlings. The DREB2 genes encode transcription factors with major roles in responses to environmental stresses, including dehydration. They bind to C-repeat motifs, known as Drought-Responsive Elements, that are indeed enriched in the promoters of genes up-regulated by PI-PLC pathway inhibitors. PA can also be produced by phospholipases D (PLDs). We show that the DREB2 genes that are up-regulated by PI-PLC inhibitors are positively or negatively regulated, or indifferent, to PLD basal activity. Our data show that the DREB2 genetic pathway is constitutively repressed in resting conditions and that DGK coupled to PI-PLC is active in this process, in suspension cells and seedlings. We discuss how this basal negative regulation of DREB2 genes is compatible with their stress-triggered positive regulation.